The role of traditional industries in the development of tourism in Algeria: An analytical study in Bordj Bou Arreridj - GASSA, Amina; BENGEUTTAF, Ahmed (Journal of Human Sciences, 2025)
This paper explores the role of traditional industries and handicrafts in supporting tourism development in Algeria, with a specific focus on the Wilaya of Bordj Bou Arreridj. Through a conceptual and analytical approach, the study examines how artisanal practices contribute to enriching the cultural tourism experience and strengthening regional identity. Drawing on official reports and sectoral analysis, the research highlights the strategic importance of crafts in shaping sustainable tourism models. The findings suggest that integrating traditional industries into tourism development plans can boost local economies, preserve cultural heritage, and enhance destination appeal. Key recommendations include improving institutional support, investing in artisanal infrastructure, and promoting collaboration between public and private stakeholders to ensure long-term impact and national visibility for the sector.